‘Langen Katresnan’ Video Animasi dengan Tema Ramayana Episode Penculikan Shinta - Ika Yulianti (Rekam: Jurnal Fotografi, Televisi, Animasi)
Ramayana story has been widely known in Indonesian society since centuries ago. This story has been disseminated from generation to generation. The story is familiar to the public in the form of this kakawin often staged in the form of performing arts, dramatari, puppet performances, as well as in the form of puppet or sculpture. Ramayana story has a lot of episodes, but in the creation of this animated video work taking Shinta kidnapping episode. This animated video works explored the form of characters and stories, as well as collaborate with dance, heater and musical arts. Kidnapping of Shinta’s story became the basis of the principal narrative in the creation of animated video with the theme of Ramayana episode kidnapping Shinta ‘Langen Katresnan’ which then developed in accordance with the ideas and concepts. It also supports the creation of new work that promotes originality of the work. This animated video works using two-dimensional techniques. This is actually a reference to that puppet animation that was first recognized by earlier ancestors.Keywords: puppet, Ramayana, animation